2018
DOI: 10.3390/plants7030067
|View full text |Cite
|
Sign up to set email alerts
|

Chiricaspi (Brunfelsia grandiflora, Solanaceae), a Pharmacologically Promising Plant

Abstract: This study’s objective was to evaluate the rescued traditional knowledge about the chiricaspi (Brunfelsia grandiflora s.l.), obtained in an isolated Canelo-Kichwa Amazonian community in the Pastaza province (Ecuador). This approach demonstrates well the value of biodiversity conservation in an endangered ecoregion. The authors describe the ancestral practices that remain in force today. They validated them through bibliographic revisions in data megabases, which presented activity and chemical components. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Previous research [77] has shown that some botanical practices are unique in this indigenous community. These practices were never registered and could offer significant progress in various medical fields [81]. Conservation of this traditional knowledge must be taken into account [82] and is a priority according to several international agreements [83].…”
Section: Context Of the Fddmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research [77] has shown that some botanical practices are unique in this indigenous community. These practices were never registered and could offer significant progress in various medical fields [81]. Conservation of this traditional knowledge must be taken into account [82] and is a priority according to several international agreements [83].…”
Section: Context Of the Fddmentioning
confidence: 99%
“…Social and economic justice refers to the exploitation of territories and military occupation (which is often exercised with strong repression and violence on indigenous peoples, in order to obtain raw materials and control the territory) [102]. It is also possible to question aspects related to the need to conserve biodiversity [103][104][105] and, at the same time, the importance of research for knowledge and the development of new products to improve the quality of life of human beings [81]. For patents, in the field of ethnobotany, the main beneficiaries are usually pharmaceutical companies, which in many cases take advantage of the botanical knowledge that communities have on the use or application of plants and their components with little or no impact in terms of economic benefits on indigenous communities [106,107].…”
Section: Reflection In Sl Activitymentioning
confidence: 99%
“…Ever since ancient times, people have looked for drugs in nature to face different diseases. Brunfelsia grandiflora is an excellent example of folk medicine used for ages with successful results against rheumatism, arthritis, cold, tiredness, pain of ovaries, sexual potency, pain in bones, laziness, and cancer of uterus [ 2 ], although limited scientific studies confirm these effects [ 10 , 11 ]. Even in our time, when there is increasing awareness of the importance of diet quality to prevent chronic disease, and although the main sources of phenolic compounds are fruits and vegetables, more and more studies refer to woody vascular plants, especially bark [ 12 ], directing the interest to the traditional herbal as a source of antioxidants with potential health-promoting properties.…”
Section: Resultsmentioning
confidence: 99%
“…Brunfelsia L. is a genus of flowering plants belonging to the family Solanaceae. Different Brunfelsia species have traditionally been used as an additive in the hallucinogenic drink "ayahuasca" by the indigenous cultures in the Ecuadorean Amazon region, often added to deepen the effects of the psychedelic beverage [1]. Certain Brunfelsia species are also used in the treatment of rheumatism, fever, cold, and arthritis, as well as acting as a tonic, laxative, antipyretic, anesthetic, and larvicidal agents [2,3].…”
Section: Introductionmentioning
confidence: 99%